Hubungan Tingkat Pengetahuan Ibu tentang MP-ASI, Umur PertamaPemberian dan Kesesuaian Porsi MP-ASI dengan Status Gizi Bayi Usia 7-12Bulan di Kecamatan Jatipuro Kabupaten Karanganyar - Nuranitha, Rizqia, Endang Nur Widyaningsih, S.ST.,M.Si,Med, Pramudya Kurnia, STP, M.Agr (2013)
Introduction : Complementary feeding should be started by the age of 6 months. A mother who had less knowledge level will cause problems with complementary feeding on her baby, such as premature delivery, late delivery, the frequency and the portion that is not age appropriate. Objective : To determine the correlation between maternal knowledge about complementary feeding, age of first administration and compliance portion of complementary feeding with nutritional status of infants aged 7-12 months. Methods : The study was a observational with cross sectional method. The samples in this study were 70 mothers and infants aged 7-12 months in the District Jatipuro Karanganyar. The instrument used in this study is a structured interviews were conducted to collect data on maternal knowledge level about complementary feeding, age of first administration and compliance portion complementary feeding. Z-score was used to asses nutritional status and the hypothesis test used is the Chi-square test. Results : The result shows that 74,3% of mothers were having a good knowledge level of comlementary feeding. Infants who received complementary foods at the right age were 61.4%, while infants receiving complementary foods with appropriate portion age 52.9 % and 77.1% of infants were is normal. The results show that there was nutritional status with correlation between maternal knowledge about complementary feeding (p-value = 0.004), age of first administration of complementary feeding (p-value = 0.011) and the suitability portion complementary feeding (p-value = 0.005). Conclusion : These findings suggest that mothers should continue to increase their knowledge about the importance of nutrition for the growth, development and health of their children. The mother should come to the neighborhood health center regularly every month. Moreover, mother can gain nutritional knowledge from mass media.